The Effect Of Brand Image and Promotion On The Purchase Decision Of Tony Jack Jeans Product At DNA Store South Of Tangerang - Suharni Rahayu (Publisher Cv. Inara, 2022)
This study aims to determine the effect of Brand Image on Purchase Decisions on Tony Jack's Jeans products, to determine the effect of Promotion on Tony Jack's jeans product purchase decisions and to determine the effect of Brand Image and Promotion on Tony Jack's Jeans product purchasing decisions at DNA Stores in general. simultaneous. By using the formula method of T Test and F Test. Brand Image has a positive and significant influence on Purchase Decisions where the value of tcount > ttable (5.224 > 1.986) and sig < 0.05 (0.000 < 0.05) Brand Image Variable (X1 ) partially positive effect on Purchase Decision. Promotion has a positive and significant effect on purchasing decisions where the value of tcount > ttable (8.728 > 1.986) and sig < 0.05 (0.000 < 0.05). Promotion variable (X2) partially positive effect on Purchase Decision. Brand Image and Promotion have a positive and significant influence on Purchase Decisions simultaneously where the fcount > ftable is 122.214 > 2.70 and the sig value < 0.05 or 0.000 < 0.05 means that there is a positive and significant influence between Brand Image and Promotion of Purchase Decisions. The multiple linear regression equation Y= 4.817 + 0.308X1 + 0.587X2 + e, means that the constant value is 4.817, the coefficient value of X1 is 0.308 and the coefficient of X2 is 0.587. Based on the calculation results, it is known that the coefficient of determination (R2) obtained is 0.563. This means that 56.3% of Purchase Decisions can be explained by Brand Image (X1) and Promotion (X2) variables, while 43.7% of Purchase Decisions are influenced by other variables not examined, such as Price, Service Quality and others.